Cyber–physical cloud-oriented multi-sensory smart home framework for elderly people: An energy efficiency perspective - Hossain, M. Shamim; Rahman, Md. Abdur; Muhammad, Ghulam (Journal of parallel and distributed computing, 2017)
The emerging Cyber–Physical Systems (CPSs) provide a number of services ranging from smart homes to elderly care. With a CPS, a user’s (elderly person’s) interactions with smart home appliances are sensed, collected, and shared in physical spaces. This interaction is then delivered to cyberspaces for processing in order to monitor energy efficiency. In this paper, we propose an energy-efficient cyber–physical smart home system for monitoring the elderly that uses the potential of cloud computing and big data technologies. Given that an elderly person may need assistance with the complex activities of maintaining energy efficiency, a smart multimedia-enabled middleware assistant is proposed that enables him/her to observe different energy-efficient processes, control smart home appliances through gestures, receive notifications regarding appliance statuses, and share multimedia messages with a community of interest. For data processing, robust and low-dimensional discriminative features are extracted in a server from the data available via sensors and multimedia. Events are also automatically classified in the server to assist caregiver decision-making. To save energy, an automatic switch on/off control system using speech or gesture is developed. Keywords are detected from the speech and used as control commands. Experimental results show the encouraging potential of deploying this framework at a large scale. •Our energy-efficient cyber–physical smart home system can efficiently monitor the elderly people.•Smart home event detection using multi-sensory environment to assist the caregiver for making decisions.•An automatic control system using speech or gesture is developed to save energy.•We adopted an energy-aware cloud-based framework for load balancing.•Low-dimensional discriminative features are extracted from the multimedia sensors.